Analysis and Verification of Vibration Reduction Solution for TractionConverter Control Cabinet of Locomotive - WANG Yongsheng; DING Jie; RONG Zhilin; CHENG Zhenglin; XU Shaolong; GAO Shoucong (机车电传动)
For the phenomenon of high failure rate of traction converter control cabinet, on-site vibration test and analysis werecarried out, which proved that too large vibration of control cabinet installed base was the main cause of the high failure rate. On thisbasis, the vibration reduction solution of control cabinet was proposed; simulation analysis and loading test verification was carried out.The simulation results agreed well with the loading test results, and the vibration reduction solution of control cabinet had good vibrationisolation effect with good engineering implementation and high popularization value.